Case Study of Touch ‘n Go in Malaysia: Are You a User of E-Wallet? - Mei Qi Loke; Xue Li Lok; Yuerui Ma; Maisarah Farisah Binti Fadli; B. S. Sushen; Vaishnavi N.; Ritika Yadav (AIBPM Publisher, 2022)
Touch ‘n Go is a Malaysian digital wallet and online transaction for making any payment that is available in the application. Malaysia has started to implement online payment through Touch ‘n Go which are available in the places that required money transactions such as grocery shops, restaurants and so on. We intended to examine how the six key factors: convenience, customer satisfaction, customer loyalty, e-wallet, brand awareness and service quality lead to users’ awareness of the usage of Touch ‘n Go in Malaysia. A total of 150 people participated in the online survey via Google Forms. The findings revealed the information regarding customer satisfaction with the quality of service provided and customer loyalty toward the brand. This research paper provides new insights, and some recommendations are presented to increase users’ awareness of the services provided by Touch ‘n Go. Keywords: brand awareness, convenience, customer satisfaction, customer loyalty, e-wallet, service quality